Tra2beta-Dependent Regulation of RIO Kinase 3 Splicing During Rift Valley Fever Virus Infection Underscores the Links Between Alternative Splicing and Innate Antiviral Immunity - White, Luke Adam; Bisom, Thomas C.; Grimes, Hunter L.; Hayashi, Miyuki; Lanchy, Jean-Marc; Lodmell, J. Stephen (Frontiers in Cellular and Infection Microbiology, 2022)
Rift Valley fever virus (RVFV) is an emerging pathogen that has potential to cause severe disease in humans and domestic livestock. Propagation of RVFV strain MP-12 is negatively impacted by the actions of RIOK3, a protein involved in the cellular immune response to viral infection. During RVFV infection, RIOK3 mRNA is alternatively spliced to produce an isoform that correlates with the inhibition of interferon  signaling. Here, we identify splicing factor TRA2- (also known as TRA2beta and hTRA2-) as a key regulator governing the relative abundance of RIOK3 splicing isoforms. Using RT-PCR and minigenes, we determined that TRA2- interaction with RIOK3 pre-mRNA was necessary for constitutive splicing of RIOK3 mRNA, and conversely, lack of TRA2- engagement led to increased alternative splicing. Expression of TRA2- was found to be necessary for RIOK3’s antiviral effect against RVFV. Intriguingly, TRA2- mRNA is also alternatively spliced during RVFV infection, leading to a decrease in cellular TRA2- protein levels. These results suggest that splicing modulation serves as an immune evasion strategy by RVFV and/or is a cellular mechanism to prevent excessive immune response. Furthermore, the results suggest that TRA2- can act as a key regulator of additional steps of the innate immune response to viral infection.